PERLINDUNGAN HUKUM BAGI KONSUMEN TERKAIT PEREDARAN OBAT KERAS OLEH TOKO OBAT YANG TIDAK BERIZIN DI INDONESIA - Antasia, Pramudita; Tarina, Dwi Desi Yayi (Unram Law Review, 2024)
One of the aspects of welfare that must be achieved in line with the national aspirations of Indonesia is public health, which is acknowledged as a fundamental right governed by the 1945 Constitution. However, there is a growing risk of hard drug misuse due to people's inclination to self-medicate without a prescription. Government Regulation Number 51 of 2009 and Law Number 17 of 2023 stipulate that only pharmacists with a prescription from a doctor are authorized to administer hard substances. Nonetheless, it is still common for illicit drug outlets to offer strong pharmaceuticals to customers without a prescription, which puts their health at risk. This study employs a normative juridical methodology that combines a case-based and statutory approach. Despite the legal protections for consumers regulated in Law Number 8 of 1999 (UUPK), many consumers do not understand their rights and obligations, so they are vulnerable to fraud and health risks. The findings of this research indicate the need for increased public awareness and stricter law enforcement to protect consumers from the misuse of hard drugs. As well as supervision by BPOM and the Public Health Office as an effort to control the circulation of hard drugs without a doctor's prescription, which are sold in drug stores that do not have a business license.